Analisis Kesalahan Teks Buku Pendidikan Bahasa Arab di Madrasah - Rizka A'yuna Fuadiyah; Mirwan Akhmad Taufiq (Institut Agama Islam Negeri (IAIN) Metro, 2020)
This article describes Arabic language books' standard at the madrasah ibtidaiyah level (Islamic Elementary School). Error analysis on textbook is one of the methods to determine the standard of the book. This study aimed to uncover syntactic errors and make corrections to the Arabic language books used as teaching materials at the madrasah ibtidaiyah level. This research was conducted using qualitative methods; applied language approaches in the field of nahwu (syntax). The analysis technique used a collaboration of content analysis by Rusydi and al-Rajihi. The primary data source was done using documentation from the book “Fokus: Modul Bahan Ajar K13 Bahasa Arab Untuk Madrasah Ibtidaiyah Kelas 5A” and interviews with teachers. Secondary data sources were carried out using documentation from related literature studies. There were seven forms of syntax errors, including word order, idhofah arrangement, incorrect use of vocabulary, misuse of al-ta'rif, i'rab, dhamir, error in using a verb. These errors have been corrected by relying on Arabic grammar rules so that this textbook is recommended for revision.